A study on factors that influence customer satisfaction towards service at AC Nielsen company Kuantan branch / Nurhidayah Mohamed Rodwan - Mohamed Rodwan, Nurhidayah (Faculty of Business and Management, 2008)
The study was conducted at Kuantan, the AC Nielsen Company (M) Kuantan branch.This research was targeted on customer of the AC Nielsen Company (M) Kuantan branch. The problem statement of this study is to identify the factors that influence customer satisfaction towards service at AC Nielsen Company Kuantan branch. The objectives of this study are to identify the factors that influence customer satisfaction at the AC Nielsen Company and to determine the relationship between management, relationship with the customer, quality of service and timeliness with the customer satisfaction at the AC Nielsen Company. The theoretical framework for this study consists of dependent variable and independent variable. Dependent variable for this research is customer satisfaction towards service and independent variables are the factors that influence customer satisfaction. Researcher had identified four independent variables such as management, relationship with the customer, quality of the service and timeliness that influence customer satisfaction. The numbers of population at the AC Nielsen Company Kuantan branch are 500 customers with 5 different departments. Data were collected through questionnaire that consist 7 sections and by interview with the customer of AC Nielsen. For this research, the sample size was 70 respondents. A convenience sampling technique was used as a procedure to determine the sample for this study and the result was analysed by using SPSS. Based on the findings, the results shows that three hypotheses were accepted and the one hypothesis were rejected. The researcher comes out with general recommendation in order to provide the alternative in increasing customer satisfaction towards service.